Evaluation of Mollicutes Microorganisms in Respiratory Disease of Cattle and Their Relationship to Clinical Signs. (10th June 2017) - Tortorelli, G.; Carrillo Gaeta, N.; Mendonça Ribeiro, B.L.; Miranda Marques, L.; Timenetsky, J.; Gregory, L.
Abstract : Background: Bovine respiratory disease (BRD) is an important problem in cattle production that is responsible for economic losses in dairy herds. Mycoplasma spp. are described as an important etiological agent of BRD. Hypothesis: To evaluate the occurrence of the most important mycoplasmas in the lower respiratory tract of healthy and BRD cattle in relationship to clinical signs of BRD. Animals: Sixty young dairy cattle were classified as healthy (n = 32) or cattle showing clinical signs of BRD (n = 28). Methods: Tracheal lavage samples were collected and added to tubes containing Hayflick media. Mycoplasma spp. were identified by the presence of "fried egg" like colonies, biochemical tests and polymerase chain reaction (PCR). Occurrence of Mollicutes, M. bovis, M. mycoides subsp. mycoides SC and M. dispar was evaluated. The association between clinical signs of BRD and the presence of Mycoplasma spp. also was evaluated. Results: Colonies were obtained from a 1‐year‐old BRD calf only. However, species identification was not possible. Mollicutes ( P = .035) and M. dispar ( P = .036) were more common in BRD cattle. The relationship between Mollicutes and crackle ( P = .057) was not significant. M. dispar was associated to tachypnea ( P = .045) and mixed dyspnea ( P = .003). Relationships to heart rate ( P = .062) and crackle ( P = .062) were not significant. Conclusions and clinical importance: The results confirmed the importance of mycoplasma as an etiologic agent of BRD and suggested M. dispar as part of the respiratory microbiota and its possible role in the development of BRD.